ARTUR AFSONASIDAGI ATOQLI OTLAR INGLIZ MILLIY MADANIYATINING IFODASI SIFATIDA - Джумаева, Нозима (Центр Научных Публикаций (buxdu.uz), 2024)
this article reveals the expression of English culture and values in the famous names of the Arthurian legends, which are considered the English national legend.